Enzymatically stable unsaturated hyaluronan-derived oligosaccharides with selective cytostatic properties - Klejch, Tomáš; Buffa, Radovan; Šimek, Matěj; Nešporová, Kristina; Exnerová, Andrea; Bednařík, Jiří; Brandejsová, Martina; Vágnerová, Hana; Fiala, František; Velebný, Vladimír (Carbohydrate polymers, 2024)
Hyaluronan, a linear glycosaminoglycan comprising D-N-acetylglucosamine and D-glucuronic acid, is the main component of the extracellular matrix. Its influence on cell proliferation, migration, inflammation, signalling, and other functions, depends heavily on its molecular weight and chemical modification. Unsaturated HA oligosaccharides are available in defined length and purity. Their potential therapeutic utility can be further improved by chemical modification, e. g., reduction. No synthesis of such modified oligosaccharides, either stepwise or by hyaluronan cleavage, has been reported yet. Here we show a three-step synthesis (esterification, depolymerization and reduction) of unsaturated even numbered hyaluronan oligosaccharides with carboxylates and the reducing terminus reduced to an alcohol. Particular oligosaccharides were synthesised. The modified oligosaccharides are not cleaved by mammalian or bacterial hyaluronidase and do not affect the growth of mouse and human fibroblasts. Further, MTT and NRU viability tests showed that they inhibit the growth of human colon carcinoma cells HT-29 by 20-50 % in concentrations 500-1000 μg/mL. Interestingly, this effect takes place regardless of CD44 receptor expression and was not observed with unmodified HA oligosaccharides. These compounds could serve as enzymatically stable building blocks for biologically active substances.
Keywords: Oligosaccharides; Hyaluronan Receptors; CD44; hyaluronoglukosaminidasa; oligosacharidy; buňky HT-29; Cytostatic Agents; lidé; Stability; Hyaluronan; Mice; Fragmentation; Cell Proliferation; Fibroblasts; Reduction; Animals; HT29 Cells; Humans; fibroblasty; Oligosaccharide; antigeny CD44; kyselina hyaluronová; myši; cytostatické látky; proliferace buněk; Hyaluronic Acid; Hyaluronoglucosaminidase; zvířata